2017
DOI: 10.1007/jhep10(2017)190
|View full text |Cite
|
Sign up to set email alerts
|

Holographic microstate counting for AdS4 black holes in massive IIA supergravity

Abstract: Abstract:We derive the Bekenstein-Hawking entropy for a class of BPS black holes in the massive type IIA supergravity background AdS 4 × S 6 from a microscopic counting of supersymmetric ground states in a holographically dual field theory. The counting is performed by evaluating the topologically twisted index of three-dimensional N = 2 ChernSimons-matter gauge theories in the large N limit. The I-extremization principle is shown to match the attractor mechanism for the near-horizon geometries constructed in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
135
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(141 citation statements)
references
References 80 publications
6
135
0
Order By: Relevance
“…This SCFT is dual to massive IIA SUGRA on AdS 4 ×S 6 . The large N Cardy free energy of the generalized superconformal index can be read off from the topologically twisted index [19] using (3.1) as 25) which is consistent with the above general formula. This large N Cardy free energy is supposed to account for the microstates of the dyonic rotating BPS black holes with vanishing magnetic charge for the R-symmetry in the massive IIA SUGRA background AdS 4 × S 6 .…”
Section: D2-branes Probing a Cy 3-fold Singularity In Massive Iia Strsupporting
confidence: 58%
See 1 more Smart Citation
“…This SCFT is dual to massive IIA SUGRA on AdS 4 ×S 6 . The large N Cardy free energy of the generalized superconformal index can be read off from the topologically twisted index [19] using (3.1) as 25) which is consistent with the above general formula. This large N Cardy free energy is supposed to account for the microstates of the dyonic rotating BPS black holes with vanishing magnetic charge for the R-symmetry in the massive IIA SUGRA background AdS 4 × S 6 .…”
Section: D2-branes Probing a Cy 3-fold Singularity In Massive Iia Strsupporting
confidence: 58%
“…In the small β limit, one can evaluate the integral (2.3) using the saddle point approximation as follows: 19) where N is the gauge group rank. Our effective potential is defined by…”
Section: The Hemisphere Indexmentioning
confidence: 99%
“…Namely, it has been shown that the topologically twisted index of certain field theory precisely matches the entropy function of the dual magnetically charged asymptotically AdS 4 black holes [7]. Similar microscopic explanations have now been extended to a wide ranges of contexts [8][9][10][11][12] (see the review [13] for a complete list of references).…”
Section: Introductionmentioning
confidence: 86%
“…In this case the electromagnetic deformation parameter is a discrete (on/off) deformation, namely, it can be set to c = 0 or 1 without loss of generality [16]. Various AdS 4 [17,18,19], domain-wall [20,19], and black hole [21,22,23,24] solutions have been constructed which necessarily require a non-zero electromagnetic deformation parameter c . Within this massive IIA context, the electromagnetic parameter is identified with the Romans mass parameterF 0 of the ten-dimensional theory [25], and has a holographic interpretation as the Chern-Simons level k of a three-dimensional super-Chern-Simons dual theory [26].…”
Section: Introductionmentioning
confidence: 99%